A development of conceptual model for defining users’ quality perception in product design / Nur Shahidatul Aina Muhammad Firdaus ... [et al.] - Muhammad Firdaus, Nur Shahidatul Aina; Shaharudin, Haszlin; Ahmad, Mohammad Azroll; Bonollo, Elivio; Wan Omar, Wan Noor Faaizah; Hasan, Zakiyah (Universiti Teknologi MARA, Kedah, 2020)
The perception and needs of individuals are important components in relation to meeting the quality of products in the design and development process. In general, the success of many products existing in the market is often determined by designers who are able to meet or exceed customers’ quality expectations and satisfaction. Due to the awareness of environmental elements, through the physical senses such as sight, hearing and touch, researchers have realized that customers’ use different variables to identify the quality of consumer products, including their understanding of product use and esteem functions. A basic research questions has been to study how product designers have addressed the problems and difficulties involved in translating user perceptions and needs into sustainable product design and manufacture. This paper discusses customer perceptions in relation to aspects of quality in product design and develops a conceptual model mindful of previous work detected in the literature. The research method used in this study is basically a qualitative method based on content analysis of data obtained from previous studies. The underlying objective is to analyze relevant specific variables of customers’ quality perceptions in product design and develop useful design guidelines or possible template solution tools for designers and marketers for product development and manufacture. Hence, these composite template solution tools, and associated sets of guidelines, are expected to have a positive impact on design education-primarily as valuable aids for design teachers to better explain to their students the underlying rationale and interdependent relationships in the relevant phases of the design process. It will be shown that it’s important for students, i.e., neo industrial designers, to understand user perceptions on product quality as this is fundamental to achieving a great user experience in the product design and development process in practice.